2014
DOI: 10.3389/fmicb.2014.00588
|View full text |Cite
|
Sign up to set email alerts
|

DotU expression is highly induced during in vivo infection and responsible for virulence and Hcp1 secretion in avian pathogenic Escherichia coli

Abstract: Type VI secretion systems (T6SSs) contribute to pathogenicity in many pathogenic bacteria. Three distinguishable T6SS loci have been discovered in avian pathogenic Escherichia coli (APEC). The sequence of APEC T6SS2 locus is highly similar to the sequence of the newborn meningitis Escherichia coli (NMEC) RS218 T6SS locus, which might contribute to meningitis pathogenesis. However, little is known about the function of APEC T6SS2. We showed that the APEC T6SS2 component organelle trafficking protein (DotU) coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…The strains and plasmids used in this study are listed in Table 1. The APEC strain DE719 (O2:K1) causes severe colibacillosis symptoms and high mortality in ducks and mice [14]. Bacteria were grown routinely in Luria–Bertani (LB) medium at 37 °C with aeration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strains and plasmids used in this study are listed in Table 1. The APEC strain DE719 (O2:K1) causes severe colibacillosis symptoms and high mortality in ducks and mice [14]. Bacteria were grown routinely in Luria–Bertani (LB) medium at 37 °C with aeration.…”
Section: Methodsmentioning
confidence: 99%
“…Three distinct T6SSs have been identified in APEC genomes. Among them, the APEC T6SS2, similar to NMEC T6SS, is responsible for the binding and invasion to host cells, survival, interbacterial competition and pathogenesis of APEC and NMEC [11, 1416]. As contact-dependent pathways, the T6SSs are tightly regulated by various regulatory mechanisms to ensure successful bacterial infection [17].…”
Section: Introductionmentioning
confidence: 99%
“…HD11 cells (chicken macrophage-like cell line) were derived from chicken bone marrow macrophages by transforming the avian leukemia virus ( 34 ). HD11 macrophages were kindly provided by Shaohui Wang (Shanghai Veterinary Research Institute, Chinese Academy of Agricultural Sciences) and cultured as the previously described ( 15 , 35 ). HD11 cells were cultured in RPMI 1640 media (Gibco) (at a humidified incubator for 41.5°C and 5% CO 2 ), supplemented with 10% heat-inactivated fetal bovine serum (FBS), 2 mM l -glutamine (Gibco), 1 mM of sodium pyruvate 0.1 mM of NEAA, and 10 mM HEPES.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the APEC T6SS2 component organelle trafficking protein (DotU) could elicit antibodies in infected ducks. Deletion of the dotU gene of APEC abolished hemolysin-coregulated protein 1 secretion, leading to the decreased expression of interleukin (IL)-6 and IL-8 genes in HD-11 chicken macrophages ( Wang et al, 2014 ). Another study has shown that E. coli type three effectors can manipulate PAMP/MAMP-triggered immune signaling components and acting on the evolutionary conserved cellular hubs of immune responses ( Fraiture and Brunner, 2015 ).…”
Section: Discussionmentioning
confidence: 99%